Karakteristik fisikokimia, total mikroba, dan sifat sensori serbuk limau kasturi (Citrus microcarpa) pada berbagai tingkat kematangan buah menggunakan mini spray dryer - Maulana Mubarak; Mhd Iqbal Nusa; Mohd Suhaimi Alias (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2026)
Calamansi (Citrus microcarpa) is a local fruit commodity with considerable potential to be developed into a functional food product due to its high content of bioactive compounds, particularly antioxidants. Processing calamansi into powder form through spray drying can extend shelf life and improve application versatility; however, the quality of the resulting product is strongly influenced by the maturity stage of the fruit used. This study aimed to evaluate the effect of fruit ripening stages of calamansi (Citrus microcarpa) on the physicochemical characteristics, bioactive properties, and sensory attributes of the powder produced using a Büchi B-290 mini spray dryer. Calamansi fruits were harvested at three maturity stages: green, half-ripe, and ripe. The parameters analyzed included moisture content, water activity, color values (L* and a*), total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity determined by DPPH and ABTS assays. The results revealed that fruit maturity significantly affected color characteristics and antioxidant capacity. The powder produced from green fruit exhibited the highest antioxidant activity (DPPH IC₅₀ = 5,01 mg/mL) with a TFC of 0,351 mg/mL, while ripe fruit produced a brighter color (L* = 88,69) and the highest TPC (0,412 mg/mL). Antioxidant activity decreased with increasing maturity due to the degradation of phenolic and flavonoid compounds during ripening and drying processes. These findings indicate that fruit maturity level determines the balance between functional and sensory quality of calamansi powder. Green fruit is more suitable for functional antioxidant-rich products, while ripe fruit is preferable for instant beverage applications with appealing color.